PELATIHAN PEMBUATAN ALAT PERAGA SAINS DARI BAHAN DAUR ULANG: STRATEGI KONKRET DALAM MEWUJUDKAN PENDIDIKAN BERKELANJUTAN DAN KESADARAN LINGKUNGAN MENUJU INDONESIA EMAS 2045 - Nya Daniaty Malau; Farabida Farabida; St Fatimah Azzahra; Putra Josua Silalahi; Gracia Zealfiana Simbolon; Saskia Jelita Sibuea; Putri Anjani (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2026)
This Community Service Program aimed to enhance the quality of science education and foster environmental awareness at Ketapang 3 Christian Junior High School by training participants to create educational demonstration tools from recycled materials. The initiative was designed to address two primary challenges: (1) the scarcity of adequate science teaching aids at the school, and (2) the suboptimal management of inorganic waste. The implementation methodology comprised three stages: preparation (coordination and material preparation), execution (conceptual training on waste impact and STEM principles, followed by a hands-on workshop to create 11 types of demonstration apparatus), and evaluation using a Likert-scale questionnaire. The participants included 5 teachers, 94 students, and 14 university student assistants. Evaluation results indicated a high participant satisfaction level of 82.55% (categorized as Very Satisfied). The highest scores were attributed to the aspects of knowledge and skill acquisition (84.04%) and the presenter's mastery of the material (83.19%). The program concluded that the recycling-based training model proved effective in producing curriculum-relevant teaching aids, improving science comprehension through experiential learning, and instilling values of sustainability. Participants suggested adding more activity variety and extending the hands-on session duration for future iterations. This program demonstrates significant potential for replication and adaptation in other schools, contributing to efforts to prepare a superior generation for Indonesia's Golden 2045 vision.